Recovery Determinants of Distressed Banks : Regulators, Market Discipline, or the Environment? - Koetter, Michael (IMF Working Papers; Working Paper ;, 2010)
Based on detailed regulatory intervention data among German banks during 1994-2008, we test if supervisory measures affect the likelihood and the timing of bank recovery. Severe regulatory measures increase both the likelihood of recovery and its duration while weak measures are insignificant. With the benefit of hindsight, we exclude banks that eventually exit the market due to restructuring mergers. Our results remain intact, thus providing no evidence of "bad" bank selection for intervention purposes on the side of regulators. More transparent publication requirements of public incorporation that indicate more exposure to market discipline are barely or not at all significant. Increasing earnings and cleaning credit portfolios are consistently of importance to increase recovery likelihood, whereas earnings growth accelerates the timing of recovery. Macroeconomic conditions also matter for bank recovery. Hence, concerted micro- and macro-prudential policies are key to facilitate distressed bank recovery.